FRACTURE PROPERTIES OF TITANIUM BONE IMPLANTS CORRODED BY SIMULATED BODY FLUID - Marčič, Simon; Praunseis, Anja (Journal of Energy Technology, 2024)
Titanium has been widely used for medical implants and restorations due to its excellent osseointegration, corrosion resistance, biocompatibility in biological fluids, and high resistance/weight ratio. The aim of this paper is to determine the fracture properties of two bone implants of a hip prosthesis made from commercially pure titanium and Ti-6Al-4V titanium alloy. Both bone implants were before fracture mechanics testing corroded by simulated body fluid. The presence of different microstructures along the pre-crack fatigue front has significant effects on the critical crack tip opening displacement (CTOD). The CTOD values were calculated in accordance with standard ASTM E1290-08e1. This value can be the relevant parameter for the safe servicing of hip prostheses.